Clinical Evaluation of Fully Automated Elecsys® Syphilis Assay for the Detection of Antibodies of Treponema pallidum. Issue 6 (26th May 2016) - Li, Dongdong; An, Jingna; Wang, Tingting; Tao, Chuanmin; Wang, Lanlan
Abstract : Objective: The resurgence of syphilis in recent years has become a serious threat to the public health worldwide, and the serological detection of specific antibodies against Treponema pallidum (TP) remains the most reliable method for laboratory diagnosis of syphilis. The performance of the Elecsys ® Syphilis assay, a brand new electrochemiluminescene immunoassay (ECLIA), was assessed by large amounts of samples in this study. Methods: In comparison with InTec assay, the Elecsys ® Syphilis assay was evaluated in 146 preselected samples from patients with syphilis, 1803 clinical routine samples, and 175 preselected samples from specific populations with reportedly increased rates of false‐positive syphilis test results. Discrepancy samples must be investigated by Mikrogen Syphilis recomline assay. Results: There was an overall agreement of 99.58% between two assays (Kappa = 0.975). The sensitivity and specificity of the Elecsys ® Syphilis assay were 100.0% (95% CI, 96.8–100.0%) and 99.8% (95% CI, 99.5–100.0%), respectively. The Elecsys syphilis assay displays better sensitivity (100%), specificity (99.8%), PPV (98.7%), and NPV (100%) in 2124 samples enrolled, compared with the InTec assay. Conclusion: Considering the excellent ease of use and automation, high throughput, and its superior sensitivity, especially in primary syphilis, the Elecsys ® Syphilis assay could represent an outstanding choice for screening of syphilis in high‐volume laboratories. However, more attention was still needed, or the results must be confirmed by other treponemal immunoassays. The new Elecsys ® Syphilis assay is applied to patients with malignant neoplasm or HIV infection.